KEPERCAYAAN MEMODERASI PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDUAL PADA LEMBAGA PERKREDITAN DESA - Artanaya, I Made Dwi Darma; Gayatri, . . (E-Jurnal Akuntansi, 2016)
The purpose of this study was to test the effect of accounting information system effectiveness on individual performance and to determine the moderating influence confidence in the effectiveness of the accounting information system of individual performance on Credit Institutions village in Tabanan district. This study was conducted on 11 LPD in Tabanan district. Sample in this study are 33 respondents by purposive sampling techniques, namely the determination of the sample based on the suitability of the characteristics and specific criteria. Data collection methods used questionnaire. Data analysis technique used is the technique of analysis moderating regression analysis (MRA). The results of the study prove the positive effect on individual performance and confidence on SIA to moderate the individual performance effectiveness of SIA on Village Credit Institution in Tabanan district. This shows the better confidence on SIA will increase the effectiveness of the SIA so that individual performance will increase.
Keywords: Trust, Effectiveness SIA, Individual Performance